The use of silver diamine fluoride in a children's hospital: Critical analysis and action protocol - Lluís Brunet‐Llobet; Beatriz Auría‐Martín; Yndira González‐Chópite; Pau Cahuana‐Bartra; Elias Isaack Mashala; Jaume Miranda‐Rius (Wiley, 2022)
Abstract Objectives The present critical analysis aims to propose an action protocol for the use of silver diamine fluoride (SDF) in pediatric patients in a hospital setting, especially for those who are currently awaiting hospital dental treatment under general anesthesia. Material and Methods A literature search was performed in the PubMed/MEDLINE from 2009 to 2021 using the search terms "silver diamine fluoride", "pediatrics silver diamine fluoride", "application silver diamine fluoride", and "AND" ‐ combined with terms: "potassium iodide", "properties", "adverse effects", "early childhood caries", "patient with disability", "management", "special health care needs patient". Articles that recorded the type of teeth, application protocol, the concentration of the product, and possible complications of the treatment were selected. Results Four hundred and sixteen related articles were obtained, of which 13 were finally chosen on the basis of the search criteria. The age at which the use of SDF was recommended ranged from the first year of life to 12 years, in most cases in primary teeth. The study populations varied in size from 53 to 799 patients. An analysis of the characteristics of SDF and its use in pediatric patients with dental caries was performed. The recommended concentration was 38% SDF, applied twice yearly. The main complication reported was staining. A decision algorithm was designed including SDF as an agent for caries control in patients attending the specific population of our hospital (divided into two groups: healthy children aged 0−4 years and patients with special health care needs (SHCNs) aged 0−18 years). Conclusions SDF therapy appears to be effective in the control of caries in pediatric patients. We propose an action protocol for patients with early childhood caries to reduce risk, complications, and the progression of lesions. The protocol is aimed especially at pediatric patients who also have some systemic pathology, disability, SHCNs, and/or behavioral difficulties.